KAJIAN PUSTAKA KRISTAL CAIR (CUBOSOME) SEBAGAI SISTEM PENGHANTARAN OBAT NANOPARTIKEL - Astridani Rizky Putranti; Agnes Nuniek Winantari; Ni Made Krisnadewi (MEDFARM: Jurnal Farmasi dan Kesehatan, 2022)
Cubosomes are cubic lipid-based delivery systems that can be an option for compounds that have low solubility in water belonging to BCS grades II and IV. The aim of this literature review is to get distinctive characteristics of cubosomes and the entrapment efficiency. Cubosomes was made by lipid (phytantriol, GMO) and added with stabilizer using top-down or bottom-up method. Characterization of cubosomes with instrument such as cryo-TEM (morphology), SAXS (crystalinity), and DLS (size distribution, zeta potential). The characteristic results obtained are cubic with size distribution of 100-500 nm and zeta potential values ±17 mV to 30 mV. As for entrapment efficiency generated ± 90% which indicates most drugs can enter the system.